FORMULASI MASKER GEL (PEEL OFF MASK) SARI BUAH TOMAT APEL (Licopersicum esculentum Mill) - Faradiba Faradiba; Ermina Pakki; Aulia Wati; Amelia Jabbar (Fakultas Farmasi UMI, 2012)
In this study, three formulas gel with varying polyvinyl alcohol 9%, 9,5%, and 10%. Then do the evaluation of physical stability by organoleptic examination of the test parameters, measurements of viscosity, yield value determination and pH determination before and after accelarated storage. The results obtained in the second organoleptic examination of the gel formula does not change the color, smeel and consistency before and after accelerated storage. In the viscosity measurements obtained results in the formula A were not significantly different before and after accelerated storage. Results of statistical analysis of the value of yield showed that the formula A were not significantly different before and accelerated storage. In rheogram formula A have the curves that coincide, formula B and C have seen that the curve is not too close together before and after accelerated storage. In pH determination, formula A have neutral pH of 6,9, formula B and C have pH of 6,8, so it can be concluted that two stocks is stable, but their stability is the most optimal formula A (concentration 9 %). Key words : Mask Gel, Apple Tomato